Upaya Kepolisian Resor Lampung Utara Dalam Penanggulangan Pencurian Sepeda Motor - Paisal Sari; Emilia Susanti (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
This research uses a qualitative approach to understand the efforts of the North Lampung Police in dealing with motorbike theft. Qualitative methods allow for in-depth analysis of strategies, policies and obstacles faced in addressing this problem. Preventive efforts are carried out through integrated security, appeals to the community, as well as routine patrols and raids. Repressive efforts are carried out by taking firm action against perpetrators of crimes, as well as careful investigations and inquiries into cases of theft. However, the North Lampung Police face a number of obstacles in tackling motor vehicle theft crimes. The lack of timely public reports, the difficulty of obtaining sufficient evidence, and illegal motor vehicle trafficking networks are the main challenges. Even though preventive and repressive efforts have been carried out, innovation and better cooperation between the police and the community are still needed to overcome this problem. In conclusion, the North Lampung Police have made various efforts to tackle motor vehicle theft, but are still faced with a number of obstacles. Better coordination is needed between the police, government and community to create a safer and more comfortable environment for all parties.